Effects of a minimalist shoe on running economy and 5-km running performance - Fuller, J. T.; Thewlis, D.; Tsiros, M. D.; Brown, N. A. T.; Buckley, J. D. (Journal of Sports Sciences, 2016)
The purpose of this study was to determine if minimalist shoes improve time trial performance of trained distance runners and if changes in running economy, shoe mass, stride length, stride rate and footfall pattern were related to any difference in performance. Twenty-six trained runners performed three 6-min sub-maximal treadmill runs at 11, 13 and 15 km/h in minimalist and conventional shoes while running economy, stride length, stride rate and footfall pattern were assessed. They then performed a 5-km time trial. In the minimalist shoe, runners completed the trial in less time (effect size 0.20 ± 0.12), were more economical during sub-maximal running (effect size 0.33 ± 0.14) and decreased stride length (effect size 0.22 ± 0.10) and increased stride rate (effect size 0.22 ± 0.11). All but one runner ran with a rearfoot footfall in the minimalist shoe. Improvements in time trial performance were associated with improvements in running economy at 15 km/h (r = 0.58), with 79% of the improved economy accounted for by reduced shoe mass (P < 0.05). The results suggest that running in minimalist shoes improves running economy and 5-km running performance.